Upper vena cava syndrome secondary to giant atrial myxoma - Longatto,Flávia Contreira (2018)
SUMMARY Cardiac myxoma is a benign neoplasm, which corresponds to the most common primary heart tumour, responsible for about 50% of the cases. In general, 75-80% of myxomas are located in the left atrium, 18% in the right atrium, and more rarely in the ventricles or multicentric. Right atrial myxoma, in particular, can obstruct the tricuspid valve, causing symptoms of right heart failure, peripheral oedema, hepatic congestion, and syncope. Systemic embolization occurs in 30% of cases, by either tumour fragmentation or total tumour detachment. In the present report, we present a case of a symptomatic patient, who showed a large right intra-atrial lesion, with consequent superior vena cava syndrome, and then underwent surgical resection at admission.